Resíduo da semente do urucum em rações contendo sorgo para poedeiras comerciais - Dantas, Francisco Diego Teixeira (2014)
In order to assess the effects of including the annatto seed residue (RSU) in diets containing sorghum on the utilization of nutrients of the ration, the performance and characteristics of eggs, an experiment was conducted with 288 hens lineage Lohman Brown, being distributed in a completely randomized design with six treatments and six replicates of eight birds each. Treatments consisted of a diet consisting of corn and soybean meal; ration with 100% sorghum replacing corn without adding pigmentante and the other in diets with 100% sorghum replacing corn with the addition of 2.5; 4.5; 6.5 and 8.5% annatto seed residue (RSU), respectively. Increasing levels of RSU did not affect the digestibility of nutrients, and harnessing the energy of the feed. It was also observed that there was no significant influence on the performance and parameters egg quality, except for yolk color. The inclusion of RSU promoted linear increase in yolk color assessed by colorimetric fan, and also a linear increase in the intensity values of red color (a *) and yellowness (b *) and linear reduction in lightness value (L * ) evaluated by digital colorimeter. To evaluate the economic feasibility of using the annatto seed residue also was not found significant difference among treatments for: feed cost per egg mass produced, index of economic viability and cost index. We conclude that, in diets of laying where sorghum is the main energy source, can include up to 8.5% of RSU, and can reduce the problems of yolk pigmentation with total replacement of corn by sorghum with the inclusion of RSU from 2.5%.